2016
DOI: 10.1080/15287394.2016.1171988
|View full text |Cite
|
Sign up to set email alerts
|

Individual and molecular level effects of produced water contaminants on nauplii and adult females of Calanus finmarchicus

Abstract: In the Barents Sea region new petroleum fields are discovered yearly and extraction of petroleum products is expected to increase in the upcoming years. Despite enhanced technology and stricter governmental legislation, establishment of the petroleum industry in the Barents Sea may potentially introduce a new source of contamination to the area, as some discharges of produced water will be allowed. Whether the presence of produced water poses a risk to the Arctic marine life remains to be investigated. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Mechanisms of barium toxicity to water fleas will be dependent on the barium form. Precipitated barium sulfate may be ingested by the water fleas, as has been observed in marine copepods (Jensen et al 2016), in which it has no nutritional value and may obstruct the digestive tract. Barium is a physiological antagonist for potassium, and it is thought that cells become deficient in potassium when barium blocks the potassium channel of the Na þ /K þ pump in the cell membrane, resulting in reduced excitability of muscle fibers and muscle paralysis (Oskarsson 2014).…”
Section: Toxicity Of Barium To Water Fleasmentioning
confidence: 93%
“…Mechanisms of barium toxicity to water fleas will be dependent on the barium form. Precipitated barium sulfate may be ingested by the water fleas, as has been observed in marine copepods (Jensen et al 2016), in which it has no nutritional value and may obstruct the digestive tract. Barium is a physiological antagonist for potassium, and it is thought that cells become deficient in potassium when barium blocks the potassium channel of the Na þ /K þ pump in the cell membrane, resulting in reduced excitability of muscle fibers and muscle paralysis (Oskarsson 2014).…”
Section: Toxicity Of Barium To Water Fleasmentioning
confidence: 93%
“…Transcriptomic analysis was performed using Agilent custom 60,000-feature D. magna oligonucleotide microarrays and 50 ng input RNA according to Agilent's standard protocol "One-Color Microarray-Based Gene Expression Analysis, version 6.5", with modifications (Song et al, 2016). Raw microarray data (signal intensity) was extracted from scanned images using the Feature Extraction software v10.7 (Agilent), and data corrected for baseline variance (normexp method), inter-array variance (quantile method), filtered for low expression probes and technical replicate probes merged using the Bioconductor package LIMMA (Smyth, 2005) in the R statistical environment v3.1.2, as previously described (Jensen et al, 2016).…”
Section: Microarray Gene Expression Analysismentioning
confidence: 99%
“…Among all OMICS approaches, transcriptomics is the most frequently used in various multiple stressor studies and has proven to be a powerful tool for MoA characterization and toxicity pathway identification (e.g. ref 14,15 ). Altenburger and co-workers 12 critically reviewed the use of OMICS in 41 mixture toxicity studies in the period of 2002 to 2011 and reported that half of the studies employed transcriptomics for elucidating the combined toxicity at the molecular level.…”
Section: ◼ Introductionmentioning
confidence: 99%